Food‐energy‐water nexus to mitigate sustainability challenges in a groundwater reliant agriculturally dominant environment (GRADE). Issue 1 (28th September 2017) - Uddameri, Venkatesh; Reible, Danny
Abstract : Groundwater reliant and agriculturally dominant environments (GRADEs) utilize exhaustible aquifer resources to supply food and fiber demands. The sustainability of these GRADES is threatened by over‐exploitation of fresher groundwater resources. There is an interest in exploring deeper brackish groundwater resources to sustain agricultural based economies in these regions. Using the southern high plains of Texas (SHP) as a test‐bed, the interlinkages between food‐energy‐water on improving water resiliency through brackish groundwater development is explored. Three scenarios—(1) direct use of deeper formations; (2) blending deeper and shallower groundwaters and 3) desalination of blended resources were evaluated in a spatially explicit manner. The results indicate that direct reuse of deeper water is possible over 30% of the study area, but it is not available in areas of critical need. The parameters limiting the suitability of deeper groundwater for agriculture in the order of decreasing importance are EC > TDS > SAR > B > Na > Cl. Simple blending of water from deeper and shallower aquifers improve water quality over roughly 900, 000 acres. While blending greatly reduces the specific ion toxicities caused by sodium absorption ratio (SAR) and boron (B), the limitations of total dissolved solids (TDS) cannot be overcome. The over‐burden pressures in the deeper confined aquifer somewhat alleviate the blending energy requirements, especially in the southern portions of SHP. Desalination increases the energy requirements by several fold and is not suitable to sustain current agricultural practices which are focused mostly on lower valued staple crops. Using desalinated water for municipal and industrial uses can help ameliorate the stresses on the Ogallala Aquifer and enhance its longevity. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 21–36, 2018 Novelty or Significance : The study is focused on the linkages between food, energy and water in groundwater dependent agricultural economies. Using the Southern High Plains of Texas as a test‐bed, the work evaluates whether a deeper brackish groundwater resource (Dockum geological unit) can be used to augment water supplies to sustain intensive agricultural production. The study identifies various factors that limit the use of this deeper resource and quantifies the energy footprint associated with three progressively complex approaches to improve water resiliency in the region and prolong the life of the Ogallala Aquifer.